Septic arthritis caused by Mycoplasma hominis in a patient with systemic lupus erythematosus. Issue 1 (19th January 2022) - Hum, Ryan Malcolm; Iftikhar, Hajira; Tang, Elaine; Ho, Pauline
Abstract : Mycoplasma hominis is one of the most common commensal organisms of the genitourinary tract. Immunocompromised patients are susceptible to developing severe infections secondary to M. hominis, and rarely, septic arthritis. This case report describes the occurrence of septic arthritis secondary to M. hominis in a 27-year-old woman with systemic lupus erythematosus (SLE), who presented with a 2-week history of left elbow swelling and tenderness, elevated inflammatory markers and joint aspiration findings consistent with infection. Serial blood cultures were negative. She was treated with flucloxacillin; however, failed to respond and so doxycycline was added to cover for atypical organisms. Subsequently, PCR analysis from the joint aspirate found M. hominis on day 16. Fortunately, doxycycline was an effective treatment for this atypical organism. This case outlines the importance of considering atypical organisms such as M. hominis as a cause of septic arthritis in immunosuppressed patients especially those with SLE.